A new species of Torenia (Linderniaceae) from Gabon, remarks on Torenia mannii Skan, and a key to the African and Madagascan Torenia species - Fischer, Eberhard; Lachenaud, Olivier (Phytotaxa, 2013)
The new species Torenia daubyi from Gabon is described and illustrated. It is closely related to T. mannii from which it differs in the smaller and relatively broader leaves, the broader calyx wings, and the shorter corolla. From T. silvicola it differs in the acute calyx lobes, broader calyx wings, and the filaments of the abaxial stamens bearing a clavate appendage. A key to the African and Madagascan species of Torenia is provided and the rediscovery of Torenia mannii, hitherto only known from the type, is reported.